Propolis from the Monte Region in Argentina: A Potential Phytotherapic and Food Functional Ingredient - Zampini, Iris Catiana (2021)
The aim of this review is to provide overall information on Argentine propolis and to shed light on its potential, especially the one from the Monte region so as to support future research in the field. Around 1999, the Argentine propolis began to be chemically and functionally characterized to give it greater added value. Because Argentina has a wide plant biodiversity, it is expected that its propolis will have various botanical origins, and consequently, a different chemical composition. To date, five types have been defined. Based on their functionality, several products have been developed for use in human and veterinary medicine and in animal and human food. Because the Argentine propolis with the greatest potential is that of the Monte eco-region, this review will describe the findings of the last 20 years on this propolis, its botanical source (Zuccagnia punctata Cav.), its chemical composition, and a description of markers of chemical quality (chalcones) and functionality. Propolis can regulate the activity of various pro-inflammatory enzymes and carbohydrate and lipid metabolism enzymes, as well as remove reactive oxygen and nitrogen species. Consequently, it can modulate metabolic syndrome and could be used as a functional ingredient in food. Furthermore, hydroalcoholic extracts can act against human and animal pathogenic bacteria and human yeast, and mycelial pathogenic fungi. The ability to stop the growth of post-harvest pathogenic bacteria and fungi was also demonstrated. For this reason, Argentine propolis are natural products capable of protecting crops and increasing the lifespan of harvested fruit and vegetables. Several reports indicate the potential of Argentine propolis to be used in innovative products to improve health, food preservation, and packaging. However, there is still much to learn about these natural products to make a wholesome use of them.